Electron dynamics and metastable species generation in atmospheric pressure non-equilibrium plasmas controlled by dual LF–RF frequency discharges - Yu, Yilin; Zhang, Zhonglin; Nie, Qiuyue; Zeng, Jiacheng; Zhao, Zhibo; Wang, Xiaogang (Frontiers in Physics, 2023)
In this work, we report an approach to control electron dynamics and metastable species generation and enhance the density of atmospheric pressure non-equilibrium plasmas by using dual-frequency excitation sources. The atmospheric dielectric barrier discharge (DBD) of an α-mode radio frequency (RF = 5 MHz) discharge controlled by a low-frequency (LF = 50 kHz) bias is studied based on a one-dimensional (1D) fluid model. Results show that the variation in amplitude ratio of RF and LF modulates the electron dynamic process, resulting in different spatial distributions of electron and metastable particle densities. Moreover, it is further shown that the electron density is substantially increased when the LF component voltage amplitude is larger than 300 V for the initial setting. The discharge process is characterized by fast Fourier transform of the spatio-temporal evolution of the electron power absorption and discharge current. As the LF is applied, three-wave interactions induced by LF and RF coupling are clearly observed, where the sum and beat frequencies between LF and RF are increased, which results in a substantial increase in the electron density. On the other hand, the high RF harmonics, especially for the fundamental and the third harmonic components, are suppressed when increasing the LF component. This work demonstrates that dual-frequency excitation is efficacious to modulate the electron dynamic behaviors and metastable species generation of atmospheric pressure plasma, which can provide a possible approach of optimizing plasma parameters.